MESSIANISMO - DE RUTE AO BRASIL CONTEMPORÂNEO: SOFRIMENTO E ESPERANÇA - Kitzinger, ângela Maringoli (2011)
This study analyzes the existing relationship between the subjects dialogued by the writer of the book of Rute (4,1-12) and the books that are part of the composition of the Deuteronomistic History.There were three proposals, each one with its own way to see the situation, the mission and the organization of the people.The first one belongs to Joshua and Zerubbabel (Ezra 3,1-13).The second of Ezra (Ed 9,1-10,44) (Ne 8,1-18) and the third of Nehemiah (5,1-19). It was really a challenge punctuating this pericope in this context. Firstly it was placed at the moment of the History of Israel, living deeply the after-exile, with the return of the deportees from Babilônia during the national restructuration of Judá. Afterwards, the personages were placed in their due social papers. The people of the land stayed in Judah and the surrounding areas. The social injustices were many: the peasants were being dispossessed of its own lands, by the Jewish brothers who had arrived from Babilônia (Ne, 51-5).These same Jewish brothers were those that had loaned money to the people of the land and had charged the payment with usury. The scene was a discouraging one. The problems were endless and of all the types. Poverty and hunger were increasing (Ag 1,6) the poor, the foreigners and the widows survived because of spills (Ruth 2.2)